Vous êtes sur la page 1sur 4

10

10 3 5

2 5

P Q

10

10 10

f : x

f(x) = e x 2 .

 x → −f (x) x → f (x) + 2 x → f (x + 3) x → f (2x) − 2
y
f(x) + 2
3
2
f(x +
3)
f(x)
1
x
−5
−4
−3
−2
−1
0 1
2
3
−f(x)
−1
f (2x)
− 2
−2

f

f(x) =

e x

1 + x

f

f f f (x) = e x (1 + x 2 )

(1 + x) 3

f f f

f f f

f −∞

f +

x = 1 x = 2

f x = 1 x = 2

f R \ {−1}

lim

x→−∞

e

x

1 + x = 0,

lim

x<1

x→−1

e

x

1 + x = −∞,

lim

x>1

x→−1

e

x

1 + x = +

et

lim

x+

e

x

1 + x = +

+ e x x +

f (x) =

xe x

(1 + x) 2

f (x) = (e x + xe x )(1 + x) 2 xe x 2(1 + x) = (e x + xe x )(1 + x) 2xe x

((1 + x) 2 ) 2

(1 + x) 3

e x (1 + x 2 )

=

(1 + x) 3

.

f f f f f (x) (1 + x) 3 f ] − ∞, 1[ ] 1, +[

f (x) x f

 −∞ −1 0 +∞ f − || − 0 + 0 || +∞ +∞ f || −∞ || 1

f x = 0

x f (x) = 0 f y = 0

lim

−∞

lim

x→−∞

f(x)

x

= + e x x 2 +

f +

e
e
x = 1 y =
4 x + 4
0 =
e
4 x + 4
e
x = −1
x = 2 y = 2e 2 x − e 2
9
9
1
0 = 2e 2
− e 2
x =
2
f x = 1 x = 2
9
9
y
= 2e 2
1
y
(x
9
2 )
3
e
y
=
4 (x +
1)
2
y = 1
1
x
0
−5
−4
−3
−2
−1
1
2
3
4
−1
−2
x = −1

R y (x) = 3y(x)

x

xe 2x

y (x) = 3y(x) + xe x

R y (x) = 3y(x)

x

C e 3x C

xe 2x dx =

x 2 e 2x dx = x e 2x

1

2

1 × 2 e 2x dx = x e 2x 4 e 2x = x

1

2

1

2

x xe 2x x

x

2

1

4 e 2x

1

4 e 2x

C(x) e 3x C (x) e 3x =

x

xe x C (x) = xe 2x C : x

x x

y (x) = 3y(x) + xe x x B e 3x + x

B

4 e 2x

4 1 e x

x

2

1

2

1

4 e x

2

C

z 2 = 2 + 2 3 i.

z z

z = a + i b z 2 = 2 + 2 3 i

a 2 b 2 = 2 2ab = 2 3

|z 2 | = | − 2 + 2 3 i|

a 2 b 2 = 2 2ab = 2 3 a 2 + b 2 = 4 + 12 = 4

a 2 b 2 = 2 2a 2 = 4 2 = 2 ab > 0

a 2 = 1 b 2 = 4 1 = 3 ab > 0

= ±1 = ± 3 ab > 0

b

a

z 1 = 1 + 3 i z 2 = 1 3 i

z 1 z 2 2 z 1 π z 2 2π

3

3

z 1 = 2e i π

3

=

2(cos( π ) + i sin( π )) z 2 = 2e i 2π

3

3

3

=

2(cos(2π ) + i sin(2π ))

3

3

(u n ) nN

a b

u 0 = a, u n+1 = 3u n + b

n 0

n 0 v n

= u n +

b

2

v n+1 v n

(v n ) nN q

u n = (a +

b

2

)q n b

2

n

a b u 1 = 0 u 2 = 1

(w n ) n0 q n 0 w n+1 = qw n

n 0 v n+1 = 3v n (v n ) nN q = 3

(v n ) nN q = 3 v n = v 0 3 n n 0

v 0 = a +

b

2

u n = (a +

b

2

)q n b

2

n 0

3(a + 9(a +

1

a = 3

b

2

b

2

)

)

− − b = 1

= 0

b

2

2

b = 1

3a + b = 0 1 9a + 4b =

3a + b = 0 b = 1